2020
DOI: 10.35366/95680
|View full text |Cite
|
Sign up to set email alerts
|

Situación de la epilepsia en México y América Latina

Abstract: México LTE 19.5 (IC 95% 8.5-34.8) AE 4.0 (IC 95% 2.3-6.5) Guatemala LTE 17.3 (IC 95% 3.3-42.0) AE 11.3 (IC 95% 2.6-26.1) Ecuador LTE 17.1 (IC 95% 12.4-22.5) AE 11.3 (IC 95% 7.0-16.6) Brasil LTE 13.0 (IC 95% 8.7-18.1) AE 6.7 (IC 95% 4.8-9.0) Bolivia LTE 12.6 (IC 95% 10.6-14.8) AE 11.1 (IC 95% 9.2-13.4) Uruguay* LTE 9.1 (IC 95% 5.4-14.4) AE no data Cuba* LTE 7.5 (IC 95% 3.5-10.0) AE no data Argentina LTE 4.6 (IC 95% 2.1-8.0) AE 3.2 (IC 95% 2.0-4.5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Seizure prevalence in Latin America varies according to geographic area and ranges from 3.9 to 42.2 per 1000 persons. 17 Meanwhile, incidence of unprovoked seizures has been reported to be of 23–61 per 100 000 person‐years. 18 , 19 Although not directly comparable with these estimates, the extremely low incidence observed in our study does not suggest causality between COVID‐19 vaccination and seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seizure prevalence in Latin America varies according to geographic area and ranges from 3.9 to 42.2 per 1000 persons. 17 Meanwhile, incidence of unprovoked seizures has been reported to be of 23–61 per 100 000 person‐years. 18 , 19 Although not directly comparable with these estimates, the extremely low incidence observed in our study does not suggest causality between COVID‐19 vaccination and seizures.…”
Section: Discussionmentioning
confidence: 99%
“…When excluding patients with history of epilepsy and with a competing cause for seizures, the events are even rarer, with fewer than two cases per million doses for any given vaccine. Seizure prevalence in Latin America varies according to geographic area and ranges from 3.9 to 42.2 per 1000 persons 17 . Meanwhile, incidence of unprovoked seizures has been reported to be of 23–61 per 100 000 person‐years 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Epilepsy is one of the most common neurological diseases, affecting between 50 and 65 million people of all ages, races, social classes, and geographic locations [1,3]. It is considered by some authors that around 8% of the general population will suffer an epileptic seizure throughout their life [4].…”
Section: Editorialmentioning
confidence: 99%
“…From January to September 2019, patients undergoing assessment or treatment for epilepsy accounted for 2,998,000 consultations in the medical units of the Mexican Institute of Social Security (IMSS) [5]. In [6], through the analysis of six epilepsy studies in Mexico, the prevalence rate was found to be between 3.9 and 42.2 cases per thousand inhabitants. The prevalence varied significantly by location.…”
Section: Introductionmentioning
confidence: 99%